2019
DOI: 10.1002/cne.24814
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitecture and myeloarchitecture of the entorhinal cortex of the common marmoset monkey (Callithrix jacchus)

Abstract: The entorhinal cortex (EC) is associated with impaired cognitive function such as in the case of Alzheimer's disease, Parkinson's disease and Huntington's disease. The present study provides a detailed analysis of the cytoarchitectural and myeloarchitectural organization of the EC in the common marmoset Callithrix jacchus. Data were collected using Nissl and fiber stained preparations, supplemented with acetylcholinesterase and parvalbumin immunohistochemistry. The EC layers and subfields in the marmoset seem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…4A, A+7.4). These characteristics correspond to well-described cytoarchitectural features of these areas in the marmoset (Burman et al, 2008(Burman et al, , 2011(Burman et al, , 2014b; Góis Morais et al, 2019).…”
Section: The Template Preserves Information About the Laminar Structusupporting
confidence: 84%
“…4A, A+7.4). These characteristics correspond to well-described cytoarchitectural features of these areas in the marmoset (Burman et al, 2008(Burman et al, , 2011(Burman et al, , 2014b; Góis Morais et al, 2019).…”
Section: The Template Preserves Information About the Laminar Structusupporting
confidence: 84%
“…The subicular complex shares borders with the CA1 field, and is typically divided into four parts, the subiculum (dorsal and ventral parts), the presubiculum, parasubiculum, and transitional subicular cortex (the transitional subicular cortex being located at the caudal lateral pole of the hippocampal curvature, see Paxinos & Watson, 2009; however, in earlier versions of rat atlases the transitional subicular cortex is labeled only as subiculum, e.g., Paxinos, Carrive, Wang, & Wang, 1999). The entorhinal cortex, the gateway between the remainder of the brain and the hippocampal formation, lies laterally adjacent to the parasubiculum, and while typically composed of medial and lateral cortical areas (e.g., Witter, Doan, Jacobsen, Nilssen, & Ohara, 2017), some studies have indicated that the entorhinal cortex may be comprised of several distinct cortical areas (e.g., de Góis Morais et al, 2019; Insausti & Amaral, 2008; Schultz & Engelhardt, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although a previous study subdivided marmoset EC into six fields ( de Góis Morais et al, 2020 ), the boundary between such subsegments of EC was not identified by Nissl staining alone. Thus, in the present study, EC was defined as a cortical region that was identified by a distinct layer II that was composed of densely stained, large-sized cells ( Figure 1A ), and we did not parcellate EC into medial (MEC) and lateral (LEC) parts.…”
Section: Resultsmentioning
confidence: 91%